A Longitudinal Research on the Distribution and Prognosis of Intracerebral Hemorrhage During the COVID-19 Pandemic - Lin, Gangqiang; Xu, Xueqian; Luan, Xiaoqian; Qiu, Huihua; Shao, Shengfang; Wu, Qingsong; Xu, Wei; Huang, Guiqian; He, Jincai; Feng, Liang (Frontiers in Neurology, 2022)
Purpose: Globally, intracerebral hemorrhage (ICH) is a common cerebrovascular disease. At the beginning of 2020, due to the coronavirus disease 2019 (COVID-19) pandemic, the allocation of medical resources and the treatment and referrals of patients were affected to varying degrees. We aimed to determine the characteristics and the prognoses and associated factors of patients with ICH. Patients and methods: The baseline demographic characteristics and ICH outcomes were compared between patients diagnosed with ICH between January and June 2020 (the 2020 group) and between January and June 2019 (the 2019 group). COVID-19 positive patients were excluded from the study. Thirty-day data of patients in the 2019 and 2020 group were analyzed to create survival curves for these patients. We also used regression models to identify the significant determinants of poor outcomes (modified Rankin score [mRS]: 3–6) and death. Results: The number of patients diagnosed with ICH was slightly lower in the 2020 group (n = 707) than in the 2019 group (n = 719). During the lockdown period (February 2020), the admission rates for ICH decreased greatly by 35.1%. The distribution of the patients’ domicile (P = 0.002) and the mRS (P <0.001) differed significantly between the years. The survival curve revealed that the highest risk of death was in the acute stage (especially in the first 5 days) of ICH. At 30 days, mortality was 19.8% in February 2019 and 29.4% in February 2020 (P = 0.119). Multivariate analysis revealed age, baseline mRS, postoperative complications, massive brainstem hemorrhage, and creatinine as factors significantly associated with poor outcomes and death following ICH. Neurosurgery and massive supratentorial hemorrhage were only correlated with the risk of death. Conclusion: During the lockdown period, the COVID-19 pandemic caused a decrease in the admission rates and severe conditions at admission due to strict traffic constraints for infection control. This led to high mortality and disability in patients with ICH. It is necessary to ensure an effective green channel and allocate adequate medical resources for patients to receive timely treatment and neurosurgery.